Kunnostusojitustarpeen arviointi Pohjois-Suomessa - Lauhanen, Risto; Piiroinen, Marja-Leena; Penttilä, Timo; Kolehmainen, Eero (Helsinki : Suoseura, 1998)
Summary: Evaluation of the need for ditch network maintenance in northern Finland